Sanksi Pidana Terhadap Pelaku Tindak Pidana Persetubuhan Terhadap Anak Berdasarkan Putusan Nomor: 119/Pid.Sus/2016/Pn.Gin - I Putu Agus Karmawan; I Made Sepud; A.A. Sagung Laksmi Dewi (Jurnal Analogi Hukum, 2020)
Abstract—Plans for protection in law, for a child have been discussed for quite a long time in Indonesia, as well as in the global world. Children are budding, potential, and the younger generation is the successor of the nation's struggle to have a strategic role and has special characteristics and characteristics that guarantee the continuity of the existence of the nation and state in the future masses. The problem is What is the legal arrangement of criminal acts of intercourse with children? What is the criminal sanction for an agent of sexual intercourse with a child? The problem approach in this study is a normative approach with the study of written legal sources from all aspects by looking at, analyzing and interpreting, various things with theoretical characteristics, concerning legal principles, and conceptual concepts. Legal materials are sourced from legal and secondary legal materials, legal material collection techniques by way of inventorying legislation, recording, and relating to the type of research. legal analysis by using descriptive method, which describes and describes the problem. Criminal acts constitute a basic understanding in criminal law and a juridical meaning, intercourse is an act that violates the norm, the Criminal Code of Criminal Procedure, whose rules concerning, intercourse to children under the age of adults, are regulated in the Criminal Code. Sexual intercourse is regulated in Law No. 23 of 2002, Law No. 35 of 2014, and Law No. 17 of 2016 Against Child Protection with criminal penalties at the latest 5 years and a maximum of 15 years and a maximum fine of Rp. 5M (five billion rupiah).